PROSPECTS FOR THE DEVELOPMENT OF GREEN LENDING PRACTICES IN COMMERCIAL BANKS - Shuhratjon Fozilchayev Qobiljon o‘g‘li (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article examines the conceptual framework and development prospects of green lending practices within commercial banking systems. In the context of global climate change and the transition to a sustainable economy, the role of financial institutions in allocating capital toward environmentally friendly projects is analyzed. The study explores the strategic mechanisms for integrating environmental, social, and governance criteria into the credit assessment processes of commercial banks. Furthermore, the paper identifies the primary challenges hindering the expansion of sustainable finance and proposes actionable recommendations to enhance green credit portfolios, mitigate environmental risks, and foster sustainable economic growth.